Marine Aggregates In North West Europe ? Demand And Supply - Graham Singleton (International Marine Minerals Society, 2004)
Around 235 million tonnes of marine aggregates have been dredged in the last decade from the UK continental shelf alone. The current distribution of marine aggregate production licence areas in North West Europe reflects the relationship between a variety of factors such as the natural distribution of deposits of sand and gravel, the demand for aggregates, the technical capabilities of the dredging fleet and environmental considerations. Whilst the sand and gravel deposits targeted by the marine aggregate industry are generally relict and therefore geographically fixed, the remaining factors have evolved over time and will continue to do so in future. Applications for new licences must not only reflect the current situation, but anticipate future trends. The main markets for marine aggregates are the construction industry, centred around the larger centres of population and coastal protection projects along the coastline of Europe. The aggregate industry as a whole does not create demand but simply meets it. Many factors influence the overall demand for aggregates and guidance exists for those in authority and industry who need to plan for the supply of aggregates. Adequate supplies should be maintained at the best balance of social, environmental and economic cost, whilst ensuring that extraction and development are consistent with the principles of sustainable development.